Fatigue dan Depresi Terbukti Menurunkan Kualitas Tidur Pasien Gagal Ginjal Kronik yang menjalani Hemodialisis - Muhammad Awaludin; Utami Sasmita Lestari; Nur Anindhita Kurniawaty Wijaya; Muhamad Nurmansyah (FORIKES, 2023)
Fatigue is a common symptom in patients with chronic diseases such as chronic kidney failure which is characterized by symptoms of mental weakness, physical weakness or both. Mental weakness can affect the psychological condition of patients which can have an impact on psychological stress such as depression. The purpose of this study was to determine the relationship between fatigue and depression with sleep quality in chronic kidney failure patients undergoing hemodialysis. This study was an observational analytical study with a cross-sectional design. The sample in this study was 102 chronic kidney failure patients undergoing hemodialysis at Prof. R.D Kandou Manado Hospital. Data were analyzed using the Chi-square test. The results showed a p-value of 0.001 for sleep quality and 0.000 for depression. Furthermore, it was concluded that fatigue and depression were related to sleep quality in chronic kidney failure patients undergoing hemodialysis.Keywords: hemodialysis; sleep quality; fatigue; depression ABSTRAK Fatigue merupakan gejala umum pada pasien penyakit kronik seperti gagal ginjal kronik yang ditandai gejala kelemahan mental, kelemahan fisik atau keduanya. Kelemahan mental dapat mempengaruhi kondisi psikologis pasien yang dapat berdampak pada stres psikologis seperti depresi. Tujuan penelitian ini adalah untuk mengetahui hubungan antara fatigue dan depresi dengan kualitas tidur pasien gagal ginjal kronik yang menjalani hemodialisis. Penelitian ini adalah penelitian analitik observasional dengan desain cross-sectional. Sampel pada penelitian ini adalah 102 pasien gagal ginjal kronik yang menjalani hemodialisis di RSUP Prof. R.D Kandou Manado. Data dianalisis menggunakan uji Chi-square. Hasil penelitian menunjukkan nilai p adalah 0,001 untuk kualitas tidur dan 0,000 untuk depresi. Selanjutnya disimpulkan bahwa fatigue dan depresi berhubungan dengan kualitas tidur pasien gagal ginjal kronik yang menjalani hemodialisis. Kata kunci: hemodialisis; kualitas tidur; fatigue; depresi